Affective resonance in response to others' emotional faces varies with affective ratings and psychopathic traits in amygdala and anterior insula - Seara-Cardoso, Ana (Soc Neurosci, 2015)
Despite extensive research on the neural basis of empathic responses for pain and disgust, there is limited data about the brain regions that underpin affective response to other people’s emotional facial expressions. Here, we addressed this question using event-related functional Magnetic Resonance Imaging to assess neural responses to emotional faces, combined with online ratings of subjective state. When instructed to rate their own affective response to others’ faces, participants recruited anterior insula, dorsal anterior cingulate, inferior frontal gyrus, and amygdala; regions consistently implicated in studies investigating empathy for disgust and pain, as well as emotional saliency. Importantly, responses in anterior insula and amygdala were modulated by trial-by-trial variations in subjective affective responses to the emotional facial stimuli. Furthermore, overall task-elicited activations in these regions were negatively associated with psychopathic personality traits, which are characterized by low affective empathy. Our findings suggest that anterior insula and amygdala play important roles in the generation of affective internal states in response to others’ emotional cues, and that attenuated function in these regions may underlie reduced empathy in individuals with high levels of psychopathic traits.